An "anomalous" triggered lightning flash in Florida. Issue 8 (25th April 2013) - Gamerota, W. R.; Uman, M. A.; Hill, J. D.; Pilkey, J.; Ngin, T.; Jordan, D. M.; Mata, C. T.
Abstract : [1] An "anomalous" rocket‐and‐wire triggered lightning flash, a flash whose leaders do not follow the triggering wire remnants to ground, is characterized via high‐speed video images at 10 and 300 kilo‐frames per second, still camera images, 66–72 MHz source locations from a Lightning Mapping Array, channel‐base current, and electric field and electric field derivative (dE/dt) measurements. This is the first anomalous flash of about 410 classically triggered flashes in north‐central Florida. The flash began with an upward positively charged leader (UPL) initiating from the tip of the upward‐moving triggering wire about 280 m above ground level. All but the bottom 17 m of wire exploded (became luminous) 37.6 ms after UPL initiation. A stepped leader initiated, likely from the top of the wire remnants, 282 m above ground level about 1.3 ms after the wire explosion and propagated downward for 2.1 ms, attaching to the top of a grounded utility pole 117 m southwest of the launching facility. The line charge density on the stepped leader is estimated to be of the order of 10 −3 C m −1 . Contrary to previously reported "anomalous" flashes in France and New Mexico (roughly 16% and 31%, respectively, of their triggered flashes), in our event, there was not a tens of milliseconds current‐zero period preceding the stepped leader, there was no observed downward dart leader in the UPL channel prior to the stepped leader to ground, and there was a failed attempt to reestablish current in the exploded‐wire channel between the UPL and ground. Key points: First Differences between the Florida Virgin air was the preferred path to ground